Advanced Study on Stability Markers in Control Theory - Egor Polilov; Olga Batiushina (Advanced Aspects of Engineering Research Vol. 4, 2021)
The linear dynamic systems stability criterion, allowing to identify the defective/failed coefficients in the characteristic polynomial at each time quantum is presented for the first time.